MEDIA, PHYSICAL ACTIVITY AND SELF-PERCEPTION OF BODY IMAGE OF STUDENTS FROM PRIVATE AND PUBLIC SCHOOLS. (Fiep Bulletin - online, 2011)
This paper aimed to know the self-perception of body image, your relationship with the media and the practice of physical activities by teenagers from private (PRS) and public School (PUS) in Timon, a city in the State of Maranhão-Brazil. 45 students of elementary schools, aged between 11 and 12 participated of this study. 20 Students came from PRS and 25 students came from PUS. The data were collected through two instruments of analysis: a body image scale (Tiggermann & Wilson-Barret), composed by 9 profiles ranging since the thinner (Profile 1) until the obesity (profile 9), and written questions about body, beauty, source of information, and the practice of physical activities. The results showed a high dissatisfaction in public and private schools, more specifically 92% in PUS, and 85% in PRS. The first group was dissatisfied about their thinness and the second one wishes weight loss. The ideal body shape chosen was the profile 5 for both groups; in the other words she wants a slim body just like the bodies of Models and Actress published mainly on TV, on magazines and on Internet because to her they are synonyms of a perfect body. Girls from PUS practice less physical activities than PRS girls, considering that the first group focus on a healthy body and the second group is seeking the weight loss. We conclude that among teenage girls there is dissatisfaction about their own body image and media has a great influence in the opinion formation of them about the ideal shape of body, making them to do physical activities aiming at weight loss and healthy body.
Keywords: Body image; Physical Activity; Media